International integration processes influence on welfare of country - Bazaluk, Oleg; Yatsenko, Olha; Reznikova, Nataliia; Bibla, Ivanna; Karasova, Nataliia; Nitsenko, Vitalii (Journal of Business Economics and Management, 2022)
The primary objective of the research is to investigate the influence of international integration processes on national welfare. Peculiarities of trade and economic liberalization of trade through mechanism of regional trade agreements (RTA) forming have been scrutinized. Integration, which develops due to RTAs, is the most important mechanism of the international cooperation in the field of economic policy. This integration is a coordination and protection mechanism, which functions in a broad spectrum of policies. An exceptional role of RTAs in reaching country economic security has been estimated. RTAs being a result of a compromise reached by protectionism and anti-protectionism forces have been grounded. Using tools of the multiple regression model, the influence of integration processes, in which Ukraine and China participate, on national economic growth rates and on GDP per capita (as major parameters reflecting national welfare level) was simulated. This allowed detecting of the positive direct dependence between the trade liberalization and economic growth rates, as well as the inverse dependence between the trade liberalization and GDP per capita, for both countries. Based on these regression models, economic growth rates and GDP per capita were predicted for next years; according to this prediction, graduate increasing of national welfare shall occur in Ukraine and China.